2013
DOI: 10.1021/ci400285z
|View full text |Cite
|
Sign up to set email alerts
|

Improved Ligand Binding Energies Derived from Molecular Dynamics: Replicate Sampling Enhances the Search of Conformational Space

Abstract: Does a single molecular trajectory provide an adequate sample conformational space? Our calculations indicate that for Molecular Mechanics--Poisson-Boltzmann Surface Area (MM-PBSA) measurement of protein ligand binding, a single molecular dynamics trajectory does not provide a representative sampling of phase space. For a single trajectory, the binding energy obtained by averaging over a number of molecular dynamics frames in an equilibrated system will converge after an adequate simulation time. A separate tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…(The 24 ps-interval at which snapshots are extracted is roughly in line with previous MM/PBSA and MM/GBSA indications, but could be reduced). [83][84][85] To study FIII, we employed a semiempirical QM/MM approach, to avoid specific parameterization of models (e.g. as required for empirical valence bond methods) 36 and limit computational cost (e.g.…”
Section: Does Selectivity For Trans-1-decalone Reduction Equal Specifmentioning
confidence: 99%
“…(The 24 ps-interval at which snapshots are extracted is roughly in line with previous MM/PBSA and MM/GBSA indications, but could be reduced). [83][84][85] To study FIII, we employed a semiempirical QM/MM approach, to avoid specific parameterization of models (e.g. as required for empirical valence bond methods) 36 and limit computational cost (e.g.…”
Section: Does Selectivity For Trans-1-decalone Reduction Equal Specifmentioning
confidence: 99%
“…We ran replicate simulations, each with slightly perturbed initial coordinates, 13 Table S2B, Supporting Information) whereas some ligands were not in the first two runs (Run 1 and 2) because, originally, the scope of the investigation was limited to selected ligands and was expanded to all ligands later.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To obtain statistically converged results, we used 40 independent simulations for each of the ligands, by assigning different starting velocities to atoms (i.e., 48 ns simulations and 1600 energy calculations in total for each ligand) . Previous studies have shown that many short independent simulations cover the phase space more effective than a single long simulation and give a more representative estimate of the statistical uncertainty . Reported uncertainties are the standard deviation over the results (averages over the 40 snapshots) from the 40 independent simulations, divided by 40.…”
Section: Methodsmentioning
confidence: 99%
“…[50] Previous studies have shown that many short independent simulations cover the phase space more effective than a single long simulation and give a more representative estimate of the statistical uncertainty. [35,[50][51][52][53][54][55] Reported uncertainties are the standard deviation over the results (averages over the 40 snapshots) from the 40 independent simulations, divided by ffiffiffiffiffi 40 p .…”
Section: Mm/gbsa Calculationsmentioning
confidence: 99%